Effects of ion bombardment on properties of d.c. sputtered superhard (Ti, Si, Al)N nanocomposite coatings - Ribeiro, E. (2002)
A d.c. reactive magnetron sputtering technique was used to deposit (Ti, Si, Al)N films. The ion current density in the substrate was varied by the" superimposition of an axially symmetric external magnetic field between the substrate and target. It was found that the variation of the magnetic field strength induced changes in the ion c~ent density in the substiate with a consequent c:hange in film properties. XRDpatternsof sputtered films revealed changes of the lattice parameter (from 0.418 nm to approx. 0.429,"~) with the increase of the ion/atom arrival rate ratio. As already reported for samples prepared by r.f. sputtering, both can be ,signed to a cubic B1 NaC1 structure, typical for TiN. The lowest lattice parameter,corresponds to a metastable pha.se where Si and Al atoms occupy Ti positions, while the highest lattice parameter correspondst o a system'w here at least a partial segregation of TiN and siNx phases already occurred, leading to the formation of a nanocompositef ilm of the:type nc-T iAlN / a- Si3N4. The mixture 'of the metastable phase with nanocomposite coating phases in some samples indicates that, in general, the segregation of TiN aDd SiNx phases is not complete. Hardness values as high as 45 GPa were; measured. Small Si additions to (Ti, Al)N coatings induce a reduction in"the pin-on-disk sliding wear rate.